Determinants of Prenatal Exposure to Polychlorinated Biphenyls (PCBs) and Polybrominated Diphenyl Ethers (PBDEs) in an Urban Population - Herbstman, Julie B. (National Institute of Environmental Health Sciences, 2007)
BACKGROUND: Recent studies have reported blood levels of polybrominated diphenyl ethers (PBDEs) in the U.S. population. Information about neonatal levels and about the relationship to polychlorinated biphenyls (PCBs) exposures is limited. OBJECTIVES: The objective was to characterize levels and determinants of fetal exposure to PBDEs and PCBs among newborns from Baltimore, Maryland. METHODS: We analyzed umbilical cord blood for eight PBDEs and 35 PCBs from infants delivered at the Johns Hopkins Hospital. Maternal and infant characteristics were abstracted from medical records. RESULTS: Ninety-four percent of cord serum samples had quantifiable levels of at least one PBDE congener, and > 99% had at least one detectable PCB congener. PBDE concentrations in cord blood were similar to those reported in other studies from North America. Strong correlations were observed within but not across PCB and PBDE classes. Multivariate models showed that many factors independently predicted exposure to BDE-47, BDE-100, and BDE-153 and CB-118, CB-138/158, CB-153, and CB-180. Generally, infants of Asian mothers had lower PBDE and PCB levels, and infants of smokers had higher levels. Increased maternal body mass index was associated with lower levels of PCBs but not PBDEs. Levels of PCBs but not PBDEs were lower in births from married and multiparous mothers. Increased maternal age was associated with higher PCB levels but lower PBDE levels. CONCLUSIONS: Although many of the factors we investigated were independent predictors of both PBDE and PCB levels, in some cases the direction of associations was different. More research is needed to better understand the sources and pathways of PBDE exposure.